Post-implant care pathway: lessons learned and recommendations after 5 years of clinical implementation of hypoglossal nerve stimulation therapy. (12th December 2020) - Soose, Ryan J; Faber, Kevin; Greenberg, Harly; Boon, Maurits; Woodson, Tucker; Strollo, Patrick
Abstract: Hypoglossal nerve stimulation (HNS) therapy is now an established and widely-available obstructive sleep apnea (OSA) treatment alternative for continuous positive airway pressure (CPAP)-intolerant patients. Additionally, the HNS body of literature is robust with strong data on safety, efficacy, and durability—from the 5-year STAR Trial outcomes, to post-approval studies of independent institutions, to the multicenter ADHERE registry which recently reported outcomes on over 1, 000 patients and is poised to enroll 5, 000 HNS patients total. Nevertheless, now with thousands of implanted patients across hundreds of certified centers, and that number growing rapidly, the post-implant management of the HNS patient represents the next critical frontier. Post-implant patient management (therapy titration, troubleshooting, adjustments, and adherence monitoring) across a longitudinal care model is key to ensuring long-term therapy success and optimizing patient outcomes and health benefits. As with CPAP, patient education and close clinical monitoring are often essential to successful long-term management. Although many HNS patients are clear responders with excellent comfort and adherence as well as effective improvement in symptomatic and objective outcome measures, and even a smaller subset is clear non-responders, there is a growing body of patients somewhere in the middle: good outcomes but not great; partial but incomplete response. These are the patients in whom a standardized best-practice approach to treatment monitoring and targeted therapy modifications is likely critical to optimizing long-term outcomes.